A comprehensive understanding of enhanced condensation heat transfer using phase separation concept. (1st April 2019) - Xie, Jian; Xu, Jinliang; Liang, Cong; She, Qingting; Li, Mingjia
Abstract: A comprehensive analysis of enhanced condensation with phase separation concept is presented, for which mesh-membrane-tube (MMT) is suspended in a tube. A twill Dutch weaved mesh screen and two plain Dutch weaved mesh screens are used to fabricate MMT. Our study reveals that liquid leakage across MMT not only keeps better condensation on condenser wall, but also decreases pressure drop rise penalty. To modulate stratified-flow, the #1 MMT with smallest d p has the largest capillary force to pump liquid towards core region to expose more condenser surface with vapor, where d p is pore diameter. To modulate annular-flow, finest mesh wires of #1 MMT ensure the best wetting to liquid to prevent condenser wall from being impacted by satellite droplets. These mechanisms explain the best performance of #1 MMT, reaching a maximum heat transfer enhancement ratio of 1.82. The three MMTs share a single curve of nozzle discharge coefficient versus Reynolds number. The similar performance of #2 and #3 MMTs is due to identical d p / φ, where φ is mesh open porosity. Fine mesh wires and small mesh pores are suggested to enhance condensation heat transfer. MMT are recommended to be used in condenser tube upstream when vapor mass qualities larger than 0.1. Highlights: Mesh-membrane-tube (MMT) is suspended in tube to enhance condensation heat transfer. MMT captures droplets with fine mesh wires to resist liquid accumulation on condenser wall. MMT having smaller mesh pores enhances liquid suction from annular region to core region. The ratio of mesh pore diameter to open porosity governs liquid flow across membrane. An overall 82% improvement of heat transfer enhancement is observed, maximally.